Enterprise Environmental Risk Management in China - Wen, Feng (2020)
With China’s rapid development of industrialization and modernization, environmental risk management in Chinese enterprises becomes increasingly significant for its business operation, reputation as well as international competitiveness. Comparing to enterprise environmental risk management in developed countries and regions, Chinese enterprises generally situated at the primary stage of development of environmental risk management. This paper is aiming to discover the actuality of enterprise environmental risk management in China and expecting to provide feasible suggestions for enterprise directors and policy makers.